PENERAPAN MEDIA CANVA NARASI BERBANTUAN E-ASSESSMENT QUIZWHIZZER UPAYA PENINGKATAN SIKAP KRITIS DAN KEMAMPUAN MEMBACA KELAS IV SD - Tesha Ameli; Panca Dewi Purwati (STKIP Subang, 2024)
This study aims to improve reading comprehension of narrative texts and critical thinking skills among fourth-grade elementary students through the implementation of Problem-Based Learning (PBL) using Canva media and QuizWhizzer eassessment. The research employs a mixed-method approach with a one-group pretest-posttest design, involving 19 students from SD Negeri Winong 01. The learning process follows the five stages of PBL syntax, enhanced with interactive Canva media for narrative text presentations and QuizWhizzer for digital gamebased assessments. The results indicate a significant improvement in students' reading comprehension skills, with the average pretest score increasing from 53.68 to 75.63 in the posttest. A paired sample t-test yielded a significance value of < 0.001, confirming the effectiveness of the learning method. Canva’s visually engaging features facilitated better comprehension of the texts, while QuizWhizzer fostered student engagement during evaluations. This approach not only enhanced students' reading comprehension but also developed their critical thinking skills, providing an interactive, innovative, and modern learning experience tailored to current educational needs.